The Effect of Green Tea (Camellia Sinensis L) Steeping on Blood Glucose Levels of Mice - Ayuningtias, Wiranting; Bahri, Syamsul; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Diabetes mellitus (DM) is a chronic metabolic disorder caused by high blood sugar levels due to lack of insulin function. Insulin is a hormone that helps blood sugar enter. Insulin injections are the main therapy for treating diabetes mellitus, they are relatively expensive and long-term use can cause side effects such as hypoglycemia. Other alternatives need to be found for the treatment of Diabetes Mellitus (DM), one of which is green tea. The aim of this research was to determine the effect of steeping green tea on the blood glucose levels of mice (24 males) which were divided into 4 groups. Mice were selected using the Simple Random Sampling technique representing 4 dose groups, namely: control group, brewed green tea at a dose of 30mg/0.5cc/day, brewed green tea at a dose of 35mg/0.5cc/day and green tea. brew at a dose of 40mg/0.5cc/day. The treatment was given orally for 6 repetitions. For 15 consecutive days. Data analysis used the One ANOVA test with a significance level of 5% (p<0.05) followed by the LSD test with a confidence level of 95%. The results of the study showed that there was a significant effect on reducing glucose levels in mice. Mice given a dose of 30, 40 and 45% brewed green tea experienced a decrease in glucose levels of 43, 32 and 40.27% respectively compared to controls.